2013
DOI: 10.1089/hum.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, Localization, and External Control of Transgene Expression After Single Injection of Adeno-Associated Virus into Injured Joints

Abstract: A single intra-articular injection of adeno-associated virus (AAV) results in stable and controllable transgene expression in normal rat knees. Because undamaged joints are unlikely to require treatment, the study of AAV delivery in joint injury models is crucial to potential therapeutic applications. This study tests the hypotheses that persistent and controllable AAV-transgene expression are (1) highly localized to the cartilage when AAV is injected postinjury and (2) localized to the intra-articular soft ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Higher levels of transgene expression by synovium and cartilage were found in horses with OA (Ghivizzani et al, unpublished). These findings are consistent with prior data using rabbits (72) and rats (73) showing enhanced transduction of chondrocytes in areas of cartilage damage following intra-articular injection of AAV.…”
Section: Gene Delivery Strategiessupporting
confidence: 92%
See 1 more Smart Citation
“…Higher levels of transgene expression by synovium and cartilage were found in horses with OA (Ghivizzani et al, unpublished). These findings are consistent with prior data using rabbits (72) and rats (73) showing enhanced transduction of chondrocytes in areas of cartilage damage following intra-articular injection of AAV.…”
Section: Gene Delivery Strategiessupporting
confidence: 92%
“…Inducible promoters have been explored as a means of regulating transgene expression in joints. Although this can be achieved with TET system (73), most research has focused on the use of self-regulating promoters that respond to inflammatory stimuli within diseased joints, as first demonstrated by Maigkov et al (80). An inducible promoter based upon a series of nuclear factor kappaB (NF-jB) response elements is entering clinical trials in RA (49,81) ( Table 1).…”
Section: Long-term and Regulated Transgene Expression Within Jointsmentioning
confidence: 99%
“…Intraarticular transgene expression at 56 days suggests transduction of longer lasting cell types such as chondrocytes or fibroblasts in the joint capsule and supporting ligaments, as seen in murine joints injected with AAV. 3 Although the immune response to AAV appears to be significantly less than to similar vectors, such as adenovirus, several studies have shown limited transduction efficiency and longevity of transgene expression in animals, with titers as low as 1:4. 16,34 Few studies have evaluated the immune response, and its impact on transgene expression, after direct IA injection of AAV vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that articular tissues, including synoviocytes and chondrocytes, can be transduced through direct intraarticular (IA) injection. [2][3][4] Gene therapy techniques, which provide long-term in situ expression of repair-enhancing genes, would be superior to repeated injections or depots of peptide that are transient.…”
Section: Introductionmentioning
confidence: 99%
“…There is also the potential risk of genotoxicity, meaning the ability of gene therapy to cause a response in healthy unaffected cells and lead to toxicity. It is important to consider that the viral vectors may precipitate in other organs of the body such as brain or striated muscles and lead to long-term toxicity (Lee et al, 2013). The risks of gene therapy require detailed awareness of the acceptable risks, to ensure the safety of the patient, third parties who are involved, and the whole population and the environment.…”
Section: Risks and Concerns Under Researchmentioning
confidence: 99%